2007
DOI: 10.1111/j.1462-2920.2007.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory role of the cistrans‐isomerase and cardiolipin synthase in the membrane fluidity of Pseudomonas putida DOT‐T1E

Abstract: In Gram-negative bacteria, cell membrane fluidity is influenced by phospholipid head group composition and linked fatty acids. Exposure of Pseudomonas putida to stressing agents results in short- and long-term modifications in membrane lipids. The main adaptive change observed in response to organic solvents in the short term is the cis- to trans-isomerization of unsaturated fatty acids in a reaction mediated by cis/trans-isomerase (CTI); whereas in the long term an increase in cardiolipin content takes place.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 45 publications
7
68
0
Order By: Relevance
“…Control experiment was performed without PCBs or 3-CBA, PCB0 -PCBs were added at the time of inoculation, PCB3 -PCBs were added to three-day cultivation, CBA0 -3-CBA was added at the time of inoculation, CBA3 -3-CBA was added to three-day cultivation. Effect of PCBs and 3-CBA on membrane adaptation Previous works described an increase in saturation of membrane phospholipids in the presence of toxic organic compounds as phenol, PAHs, and organic solvents (Heipieper et al 1994;Čertík et al 2003;Dercová et al 2004;Bernal et al 2007;Mrozik et al 2010). However, information about the effect of PCBs is rarely accessible.…”
Section: Effect Of Pcbs and 3-cba On Lipid Compositionmentioning
confidence: 99%
“…Control experiment was performed without PCBs or 3-CBA, PCB0 -PCBs were added at the time of inoculation, PCB3 -PCBs were added to three-day cultivation, CBA0 -3-CBA was added at the time of inoculation, CBA3 -3-CBA was added to three-day cultivation. Effect of PCBs and 3-CBA on membrane adaptation Previous works described an increase in saturation of membrane phospholipids in the presence of toxic organic compounds as phenol, PAHs, and organic solvents (Heipieper et al 1994;Čertík et al 2003;Dercová et al 2004;Bernal et al 2007;Mrozik et al 2010). However, information about the effect of PCBs is rarely accessible.…”
Section: Effect Of Pcbs and 3-cba On Lipid Compositionmentioning
confidence: 99%
“…It was suggested that organic solvents accumulate in cellular membranes and disorganize the structures, and the resultant losses of intracellular ions and metabolites lead to cell death (19,20). Organic solvents also induce various cellular responses, including structural changes of the membrane (21,22), and upregulation or downregulation of various other genes, as revealed by transcriptomic analyses (19,23). Nonetheless, with regard to the simultaneous addition of cationic agents and alcohols, many questions remain, such as how each agent acts individually on microbes.…”
mentioning
confidence: 99%
“…3). Such multi-layered interconnected survival strategies, together with the general or specialized horizontal gene transfer systems (7,64), are key features in understanding how S. aureus has developed as such a successful pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…A general strategy among bacteria is to change phospholipid composition in response to growth phase or environmental stress such as osmolality (74), pH (31,51), temperature and the presence of organic solvents (7,73). In the 1970's, the molecular mechanism of staphylococcal salt resistance was studied, focusing on a phospholipid, cardiolipin (CL), which constitutes about 30% of the cell membrane in the stationary phase of growth (80).…”
Section: Cell Architecture Dynamics: Cell Membrane Componentsmentioning
confidence: 99%